Towards Aspects Identification in Business Process Through Process Mining - Brandão, Bruna; Santoro, Flávia; Azevedo, Leonardo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de Informação, 2015)
In business process models, elements can be scattered (repeated) within different processes, making it difficult to handle changes, analyze process for improvements, or check crosscutting impacts. These scattered elements are named as Aspects. Similar to the aspect-oriented paradigm in programming languages, in BPM, aspect handling has the goal to modularize the crosscutting concerns spread across the models. This process modularization facilitates the management of the process (reuse, maintenance and understanding). The current approaches for aspect identification are made manually; thus, resulting in the problem of subjectivity and lack of systematization. This paper proposes a method to automatically identify aspects in business process from its event logs. The method is based on mining techniques and it aims to solve the problem of the subjectivity identification made by specialists. The initial results from a preliminary evaluation showed evidences that the method identified correctly the aspects present in the process model.